PHYSICAL ACTIVITY AGAINST DEVIANT BEHAVIOR: IS IT POSSIBLE TO PREVENT AND REDUCE DEVIANCES WITH SPORT? - Al. Dimitrova, Zlatka; St. Dishkova, Maria (Journal of process management and new technologies, 2017)
This article discusses physical activity and sport as a good way to overcome deviant behavior in children. A number of characteristics of sporting activity are identified, which define it as useful not only for the physical but also for the psychological, emotional and overall development of the personality. Organized extracurricular sports activities are mentioned as a good means of organizing the leisure time of the students. Of course, sport is not a universal remedy for the problems of society and the deviant behavior of children. But it is one of the working options for prevention and overcoming deviant behavior, especially if it is a result mainly of the child’s personal characteristics such as aggression, temperamental behavior or adrenal dependence. Affiliation to the team gives the child certainty that they area member of a community where they give and receive permanent support. The pursuit of personal achievement reflects the development of the child and directs his or her energy in a positive direction. Achieved success boosts self-confidence and self-esteem that are so necessary to young people especially in teen years. Driving into discipline in sport will lead to compliance with social norms and public laws.